Feasibility of FDCT Early Brain Parenchymal Blood Volume Maps in Predicting Short-Term Prognosis in Patients With Aneurysmal Subarachnoid Hemorrhage - Wen, Lili; Zhou, Longjiang; Wu, Qi; Zhou, Xiaoming; Zhang, Xin (Frontiers in Neurology, 2022)
Purpose Aneurysmal subarachnoid hemorrhage (SAH) is accompanied by cerebral perfusion changes. We aimed to measure the parenchymal blood volume (PBV) maps acquired by C-arm flat-panel detector CT (FDCT) to assess the cerebral blood volume at an early stage in aneurysmal SAH and to explore the correlation with the outcomes at discharge. Methods Data of 66 patients with aneurysmal SAH who underwent FDCT PBV examination were retrospectively analyzed. The PBV of regions of interest, including the cortices of the bilateral frontal lobe, the parietal lobe, the occipital lobe, and the cerebral hemisphere, as well as the basal ganglia, were measured and quantitatively analyzed. The clinical and imaging data of the patients were also collected, and logistic regression analysis was performed to explore the correlation between the perfusion parameters and outcomes at discharge. Results The favorable and poor outcomes at discharge were found in 37 (56.06%) and 29 (43.94%) patients, respectively. The whole-brain PBV was significantly correlated with the Hunt-Hess grades (p < 0.005) and the WFNSS grades (p < 0.005). The whole-brain PBV of the poor prognosis was significantly higher than that of the favorable prognosis (35.17 ± 7.66 vs. 29.78 ± 5.54, p < 0.005). The logistic regression analysis showed that the PBV of the parietal lobe at the bleeding side (OR = 1.10, 95%CI: 1.00–1.20, p = 0.04) was an independent risk factor predicting the short-term prognosis. Conclusions Parenchymal blood volume (PBV) maps could reflect the cerebral blood volume throughout the brain to characterize its perfusion status at an early stage in aneurysmal SAH. It enables a one-stop imaging evaluation and treatment in the same angio-suite and may serve as a reliable technique in clinical assessment of aneurysmal SAH.